TINGKAT RISIKO KONFLIK MANUSIA DAN HARIMAU SUMATERA DI SEKITARAN HUTAN TANAMAN INDUSTRI PT. ARARA ABADI DISTRIK TAPUNG RISK LEVEL OF HUMAN AND SUMATERAN TIGERS (PANTHERA TIGRIS SUMATRAE)IN PT. ARARA ABADI DISTRIK TAPUNG INDUSTRIAL FOREST - Ahmad Rizal; Yusni Ikhwan Siregar; Dr. Nofrizal, S.Pi, M.Si (Program Pascasarjana Universitas Riau, 2021)
IUCN (International Union for Conservation of Nature) categorizes the Sumatran tiger as an endangered species in crisis, which is the highest category of extinction threat. One of the causes of the extinction of the Sumatran tiger is conflict with humans. The meeting of human activities and the roaming area of tigers in the same space creates an adverse conflict on both sides.This research was conducted in the Hutan Tanaman Industri of PT. Arara Abadi, Tapung District, located in Siak Regency and Kampar Regency, Riau Province, to be precise in Rantau Bertuah Village and Garo City Village. The research method is a qualitative approach. Primary data obtained from observations and interviews, and document studies. Secondary data obtained from literature studies are landscape maps, animal monitoring data, and biodiversity reports of PT. Arara Abadi, Tapung district. In addition, the literature study is also sourced from the Riau BKSDA wildlife monitoring data document. Result: Conflict between humans and Sumatran tigers occurred in the concession area of PT. Riau Abadi Lestari to be precise in a conservation area, in a community plantation area. The social losses that occur are in the form of psychological losses, while other losses such as human injuries or death do not occur. The economic loss was Rp. 42,000,000. In addition, some residents lost their working days to cultivate their gardens. The frequency of conflicts that occurred in Rantau Bertuah Village did not recur and conflicts that occurred in Kota Garo Village occurred repeatedly throughout 2020.Conflicts that occur in Rantau Bertuah Village are low risk. Meanwhile, the conflict that occurred in the village of Kota Garo was included in moderate risk.